The young turks and the ottoman nationalities Armenians, Greeks, Albanians, Jews, and arabs, 1908-1918 - Ahmad, Feroz (University of Utah, 2014)
RESUMEN: The years 1908 to 1918 are frequently viewed as the period when the Ottoman Empire fell into decline, but in this volume Feroz Ahmad argues that the Empire was not in decline but instead was face to face with the process of decolonization. Its colonies, stimulated by the idea of nationalism, saw the opportunity to liberate themselves, sometimes with the help of the Great Powers of Europe, who in turn saw these rebellions as an opportunity to expand their own empires. While these ethno-nationalist movements have often been described in terms of Ottoman oppressor versus conspiring nationalists, here they are presented as part of the historical process. Ahmad holds that nationalism was introduced into the Ottoman Empire during the French Revolution, providing kindling for the struggles that later emerged. The Serbs were the first to rebel and thus launched the process of decolonization and struggle against Ottoman imperialism. After the Serbs, the Greeks rebelled and with European support were able to establish their own state. From Greece the struggle against the Ottomans spread throughout the Balkans and then to Anatolia. Setting the stage with this 19th-century background, Ahmad then examines each of the nationalities in a separate chapter, beginning with the restoration of the Ottoman constitution in 1908. The Young Turks, officially known as the Committee of Union and Progress (CUP), was a Turkish nationalist political party that ruled the Ottoman Empire from this time until the end of World War I. The book illuminates the relationships and conflicts between the Young Turks and the Greek, Armenian, Albanian, Jewish, and Arab ethnic groups during this period. Placing them in their historical context